2003
DOI: 10.4049/jimmunol.170.6.3401
|View full text |Cite
|
Sign up to set email alerts
|

CTLA-4 Blockade Enhances the Therapeutic Effect of an Attenuated Poxvirus Vaccine Targeting p53 in an Established Murine Tumor Model

Abstract: p53 is overexpressed by half of all cancers, and is an attractive target for a vaccine approach to immunotherapy. p53 overexpression is frequently the result of point mutations, which leaves the majority of the protein in its wild-type form. Therefore, the majority of p53 sequence is wild type, making it a self-protein for which tolerance plays a role in limiting immune responses. To overcome tolerance to p53, we have expressed wild-type murine p53 in the nonpathogenic attenuated poxvirus, modified vaccinia vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 51 publications
3
57
0
Order By: Relevance
“…It has been shown in several animal models that CTLA-4 signalling can restrict antitumour immune responses (Leach et al, 1996;Kwon et al, 1997;Espenschied et al, 2003). Antibodies against CTLA-4 are currently being tested for their ability to treat human tumours.…”
Section: The Benefit Of Depletion or Inhibition Of Treg Cells Or Theimentioning
confidence: 99%
“…It has been shown in several animal models that CTLA-4 signalling can restrict antitumour immune responses (Leach et al, 1996;Kwon et al, 1997;Espenschied et al, 2003). Antibodies against CTLA-4 are currently being tested for their ability to treat human tumours.…”
Section: The Benefit Of Depletion or Inhibition Of Treg Cells Or Theimentioning
confidence: 99%
“…Prior studies from our laboratory have demonstrated the ability to generate p53-specific responses after immunization with modified vaccinia Ankara (MVA) expressing WT murine p53 (MVAp53; Ref. 14). Immunized mice developed vigorous p53-specific CTL responses and were able to reject small, established p53-overexpressing Meth A tumors.…”
Section: Introductionmentioning
confidence: 99%
“…MVA-expressing p53 and pp65 were generated by homologous recombination with WTMVA infection (obtained from Drs. Moss and Wyatt) and transfected pMCO3 containing an insert in BHK-21 cells (14). MVA were screened for gus marker expression and evaluated for purity and absence of WTMVA by PCR.…”
Section: Recombinant Mvamentioning
confidence: 99%
See 1 more Smart Citation
“…Based on successful preclinical murine tumor therapy models (158,159), a number of ongoing and completed clinical trials have used anti-CTLA-4 to treat patients with cancer of different histologic types. The initial reports have been encouraging, with two groups documenting significant increases in antitumor immunity in vaccinated melanoma patients following anti-CTLA-4 treatment, including the induction of some objective tumor regressions (160 -162).…”
Section: Future Approaches To Circumventing Immunoregulationmentioning
confidence: 99%